Prevalence of oro‐dental pathology in a working horse population in Egypt and its relation to equine health. (16th December 2015) - Salem, S. E.; Townsend, N. B.; Refaai, W.; Gomaa, M.; Archer, D. C.
Summary: Reasons for performing study: Oro‐dental disease can have a significant impact on equine welfare. Objectives: To determine the prevalence of oro‐dental disease and to identify risk factors for oro‐dental disorders and poor body condition scores (BCS) in a working horse population in Egypt. Study design: Cross‐sectional survey. Methods: Oro‐dental examination was performed on 450 working horses in 2 Egyptian provinces. Horse and management historical data were collected and horses were assigned to no/mild, moderate and severe dental disease categories based on findings on examination. Multivariable logistic regression and generalised additive models were used to identify risk factors for oral mucosal injuries and very poor/poor BCS, and to explore the relationship between age and different oro‐dental disorders. Results: Oro‐dental disease was common, with 45.3% and 8.4% of horses considered to have moderate and severe oro‐dental disease, respectively. None of these horses had previously undergone any form of proper dental examination and treatment by trained personnel. Oral mucosal injuries (64.2%) and sharp enamel points (79.8%) were most common. Oral mucosal injuries were significantly associated with increasing age (odds ratio (OR) 1.1, 95% confidence interval (CI) 1.01–1.1, P = 0.03), focal dental overgrowths (OR 2.4, 95% CI 1.4–4.0, P = 0.002) and sharp enamel points (OR 6.3, 95% CI 3.5–11.0, P<0.001). Very poor and poor BCS were significantly associated with severe dental disease (OR 2.6, 95% CI 1.2–5.8, P = 0.02), horses aged 16–30 years (OR 3.5, 95% CI 1.7–7.0, P = 0.001), height (OR 0.9, 95% CI 0.9–0.97, P = 0.001) and packed cell volume (OR 0.9, 95% CI 0.85–0.95, P<0.001). Conclusions: There is a need for education of working horse‐owners in Egypt about the importance of oro‐dental disease and for greater availability of veterinarians with suitable training and equipment to perform dental prophylaxis and treatment. Even simple dental prophylaxis could have a significant impact on the health and welfare of this population of working horses.